Pricing Randomized Allocations - Briest, Patrick; Chawla, Shuchi; Kleinberg, Robert; Weinberg, S. Matthew (Proceedings of the Twenty-First Annual ACM-SIAM Symposium on Discrete Algorithms)

Foreword - Gavoille, Cyril; Patt-Shamir, Boaz; Scheideler, Christian (Theory of Computing Systems)

Peer-to-peer networks based on random graphs - Mahlmann, Peter

Local, distributed approximation algorithms for geometric assignment problems - Degener, Bastian

Time Complexity of Distributed Topological Self-stabilization: The Case of Graph Linearization - Gall, Dominik; Jacob, Riko; W. Richa, Andrea; Scheideler, Christian; Schmid, Stefan; Täubig, Hanjo (LATIN 2010: Theoretical Informatics, 9th Latin American Symposium, Oaxaca, Mexico, April 19-23, 2010. Proceedings)

Brief announcement: towards robust medium access in multi-hop networks - Richa, Andrea W.; Zhang, Jin; Scheideler, Christian; Schmid, Stefan (Proceedings of the 29th Annual ACM Symposium on Principles of Distributed Computing, PODC 2010, Zurich, Switzerland, July 25-28, 2010)

A Jamming-Resistant MAC Protocol for Multi-Hop Wireless Networks - Richa, Andrea W.; Scheideler, Christian; Schmid, Stefan; Zhang, Jin (Distributed Computing, 24th International Symposium, DISC 2010, Cambridge, MA, USA, September 13-15, 2010. Proceedings)

Brief Announcement: Stabilizing Consensus with the Power of Two Choices - Doerr, Benjamin; Ann Goldberg, Leslie; Minder, Lorenz; Sauerwald, Thomas; Scheideler, Christian (Distributed Computing, 24th International Symposium, DISC 2010, Cambridge, MA, USA, September 13-15, 2010. Proceedings)

Algorithms for Sensor Systems - 6th International Workshop on Algorithms for Sensor Systems, Wireless Ad Hoc Networks, and Autonomous Mobile Entities, ALGOSENSORS 2010, Bordeaux, France, July 5, 2010, Revised Selected Papers

Selected properties of a joint congestion controller for TCP connections - Savorić, Michael; Karl, Holger; Wolisz, Adam (Providing Quality of Service in Heterogeneous Environments, Proceedings of the 18th International Teletraffic Congress - ITC-18)

ANALYSING CAPACITY IMPROVEMENTS IN WIRELESS NETWORKS BY RELAYING - Karl, Holger; MENGESHA, S. (Wireless LANs and Home Networks)

Flexible Resource Management for Self-X Systems: An Evaluation - Oberthür, Simon; Zaremba, Leszek; Lichte, Hermann Simon (2010 13th IEEE International Symposium on Object/Component/Service-Oriented Real-Time Distributed Computing Workshops)

Secure Naming for a Network of Information - Dannewitz, Christian; Golic, Jovan; Ohlman, Borje; Ahlgren, Bengt (2010 INFOCOM IEEE Conference on Computer Communications Workshops)

Asynchronous Parallel Reliefboard Computation for Scene Object Approximation - Fischer, Matthias; Jähn, Claudius; Suess, Tim (Eurographics Symposium on Parallel Graphics and Visualization (EGPGV))
We present a parallel algorithm for the rendering of complex three-dimensional scenes. The algorithm runs across heterogeneous architectures of PC-clusters consisting of a visualization-node, equipped with a powerful graphics adapter, and cluster nodes requiring weaker graphics capabilities only. The visualization-node renders a mixture of scene objects and simplified meshes (Reliefboards). The cluster nodes assist the visualization-node by asynchronous computing of Reliefboards, which are used to replace and render distant parts of the scene. Our algorithm is capable of gaining significant speedups if the cluster's nodes provide weak graphics adapters only. We trade the number of cluster nodes off the scene objects' image quality.

Evaluation of a c-Load-Collision-Protocol for Load-Balancing in Interactive Environments - Suess, Tim; Wiesemann, Timo; Fischer, Matthias (2010 IEEE Fifth International Conference on Networking, Architecture, and Storage)
Many professional cluster systems consist of nodes with different hardware configurations. Such heterogeneous environments require different load-balancing techniques than homogenous environments. The c-load-collision-protocol is able to achieve good results for data-management purposes. Using this protocol, we propose a way for load-balancing in interactive rendering environments. For this work, we implemented a parallel rendering system and took different picking strategies into account to compare the results. The advantage of our approach compared to other approaches is that we group the available nodes of a cluster into two different categories, based on the hardware abilities. Some nodes are used solely for rendering, while others serve as secondary storage and to assist the former ones by performing auxiliary calculations.

Gewichtetes c-Collision-Protokoll zur Balancierung eines parallelen Out-of-Core-Renderingsystems - Suess, Tim; Wiesemann, Timo; Fischer, Matthias (Augmented & Virtual Reality in der Produktentstehung)
Typischerweise sind die Knoten eines PC-Clusters nicht mit leistungsfähigen Grafikkarten ausgestattet. Dennoch bieten Cluster-Betreiber einige wenige Rechenknoten an, die mit Highend-Grafikkarten ausgestattet sind, um beispielsweise eine PowerWall zu betreiben. Wenn zwischen diesen unterschiedlichen Knotentypen ein schnelles Netzwerk existiert, kann die Bilderzeugung durch die Knoten mit schwacher Grafikkarte beschleunigt werden. Dabei können die unterschiedlichen Knotentypen unterschiedliche Aufgabe bearbeiten. In einem solchen heterogenen System, müssen die unterschiedlichen entstehenden Lasten auf andere Weise verteilt werden, als in einem System, bei dem alle Knoten gleich ausgestattet sind. Wir präsentieren in dieser Arbeit Lastbalancierungsmechanismen, die in einem parallelen Out-of-Core-Renderingsystem für heterogene PC-Cluster eingesetzt werden.

Cooperative feedback to improve capacity and error rate in multiuser diversity systems - an OFDM case study - Valentin, Stefan; Karl, Holger (European Transactions on Telecommunications)

Integrative Konzipierung von MID-Produkt und MID-Produktionssystem - Gausemeier, Jürgen; Dumitrescu, Roman; Gaukstern, Tobias (Frühzeitige Zuverlässigkeitsanalyse mechatronischer Systeme)

Coping with Complex Real-World Problems: Strategies for Developing the Competency of Transdisciplinary Collaboration - Domik, Gitta; Fischer, Gerhard (Key Competencies in the Knowledge Society)

A Survey of Transfer Functions Suitable for Volume Rendering - Arens, Stephan; Domik, Gitta (IEEE/ EG Symposium on Volume Graphics)

Graph Transformations and Model-Driven Engineering - Essays Dedicated to Manfred Nagl on the Occasion of his 65th Birthday

Software Engineering 2010 - Workshop Proceedings (inkl. Doktoranden Symposium), Paderborn (Germany)

Software Engineering 2010 - Proceedings, Paderborn (Germany)

Modellierung 2010, Klagenfurt (Österreich)

Proceedings of the 5th International Workshop on Model Driven Development of Advanced User Interfaces (MDDAUI 2010): Bridging between User Experience and UI Engineering

Holistic Model-Based Testing for Business Information Systems - Mlynarski, Michael (Proceedings of 3rd International Conference on Software Testing, Verification and Validation)

A Generic Meta-Model-based Approach for Specifying Framework Functionality and Usage - Christ, Fabian; Bals, Jan-Christopher; Engels, Gregor; Gerth, Christian; Luckey, Markus (Proceedings of the 48th International Conference on Objects, Models, Components and Patterns (TOOLS'10), Málaga (Spain))

Graph Transformations and Model-Driven Engineering: The Merits of Manfred Nagl - Engels, Gregor; Lewerentz, Claus; Schäfer, Wilhelm; Schürr, Andy; Westfechtel, Bernhard (Graph Transformations and Model-Driven Engineering)

Knowledge Transfer in Global Software Development - Leveraging Acceptance Test Case Specifications - Engels, Gregor; Salger, Frank (In Proceedings of the ACM/IEEE 32nd International Conference on Software Engineering (ICSE), New Ideas and Emergent Results program, May 2010, Cape Town (South Africa))

Proceedings 12. Workshop Software-Reengineering (WSR) & 2. Workshop Design for Future 2010 (DFF) - Gimnich, Rainer; Kaiser, Uwe; Momm, Christof; Quante, Jochen; Riediger, Volker; Sauer, Stefan; Trifu, Mircea; Winter, Andreas

Precise Detection of Conflicting Change Operations using Process Model Terms - Gerth, Christian; Küster, Jochen; Luckey, Markus; Engels, Gregor (Proceedings of the ACM/IEEE 13th International Conference on Model Driven Engineering Languages and Systems (MODELS'10))
Version management of process models requires that changes can be resolved by applying change operations. Conflict detection is an important part of version management and the minimization of the number of detected conflicts also reduces the overhead when resolving changes. As not every syntactic conflict leads to a conflict when taking into account model semantics, a computation of conflicts solely on the syntax leads to an unnecessary high number of conflicts. In this paper, we introduce the notion of syntactic and semantic conflicts for change operations of process models. We provide a method how to efficiently compute conflicts, using a term formalization of process models. Using this approach, we can significantly reduce the number of overall conflicts and thereby reduce the amount of work for the user when resolving conflicts.

Detection of Semantically Equivalent Fragments for Business Process Model Change Management - Gerth, Christian; Luckey, Markus; Küster, Jochen; Engels, Gregor (Proceedings of the IEEE 7th International Conference on Services Computing (SCC'10))

Enriching RUP with key success factors for large-scale custom software development projects - Heinemann, Marianne; Duwe, Bettina; Engels, Gregor (Software & Systems Engineering Essentials (SEE) 2010)

Auswahl projektspezifischer Vorgehensstrategien - Heinemann, Marianne; Engels, Gregor (Integration von Vorgehensmodellen und Projektmanagement)

Computergestützte traumatherapeutische Behandlungsmöglichkeiten bei Verkehrsunfallopfern von Kinder und Jugendlichen - Huck, Wilfried; Alakbarov, Alexej; Domik, Gitta; Radkowski, Rafael; Tölke, Roswitha; Mikus, Ann-Cathrin; Geisen, Silke (12. Jahrestagung der Deutschsprachigen Gesellschaft für Psychotraumatologie (DeGPT))

Dynamic Computation of Change Operations in Version Management of Business Process Models - Küster, Jochen; Gerth, Christian; Engels, Gregor (Proceedings of the 6th European Conference on Modelling Foundations and Applications (ECMFA'10))
Version management of business process models requires that changes can be resolved by applying change operations. In order to give a user maximal freedom concerning the application order of change operations, position parameters of change operations must be computed dynamically during change resolution. In such an approach, change operations with computed position parameters must be applicable on the model and dependencies and conflicts of change operations must be taken into account because otherwise invalid models can be constructed. In this paper, we study the concept of partially specified change operations where parameters are computed dynamically. We provide a formalization for partially specified change operations using graph transformation and provide a concept for their applicability. Based on this, we study potential dependencies and conflicts of change operations and show how these can be taken into account within change resolution. Using our approach, a user can resolve changes of business process models without being unnecessarily restricted to a certain order.

A Meta-Method for Defining Software Engineering Methods - Engels, Gregor; Sauer, Stefan (Graph Transformations and Model-Driven Engineering)

Erweiterung des TPI-Modells zur Reifegradbewertung unter Berücksichtigung von projekteigenen Anforderungen - Sancar, Yavuz; Schumacher, Claudia (Proceedings of the Conference on Software & Systems Engineering Essentials 2010 (SEE 2010), Köln (Germany))

Assessments in Global Software Development: A Tailorable Framework for Industrial Projects - Salger, Frank; Engels, Gregor; Hofmann, Alexander (Proceedings ACM/IEEE 32nd International Conference on Software Engineering, Software Engineering in Practice Track, Cape Town, South Africa (ICSE'10))

SheetDiff: A Tool for Identifying Changes in Spreadsheets - Chambers, Chris; Erwig, Martin; Luckey, Markus (Proceedings of the 26th IEEE Symposium on Visual Languages and Human-Centric Computing 2010 (VL/HCC 2010))

Model-driven Development of Advanced User Interfaces - Van den Bergh, Jan; Meixner, Gerrit; Breiner, Kai; Pleuß, Andreas; Sauer, Stefan; Hussmann, Heinrich (Proc. 28th International Conference on Human Factors in Computing Systems (CHI 2010))

Transfer of Testing Research from University to Industry: An Experience Report - Güldali, Baris; Sauer, Stefan (online Proc. of International TestIstanbul Conference 2010 (URL: www.testistanbul.org/presentations.html))
Software Quality Lab (s-lab) is an open multi-private-public partnership institute for knowledge and technology transfer. In s-lab, partners from industrial software development closely cooperate with research groups of the University of Paderborn. Together with partners from industry, s-lab develops and evaluates constructive and analytical methods and tools of software engineering for obtaining high-quality software. Testing plays an important role in analytical quality assurance within s-lab’s activities. Thereby our main focus lies on the development of testing methods, test automation tools and test management concepts for the individual needs of the industrial partners. Because of the different requirements of the university and the industry; the cooperation involves some challenges, e.g. defining projects aiming at the commercial interests of the industry and addressing interesting research questions. In this paper, we give an overview of testing activities in s-lab and address targets and challenges of the cooperative work between industry and university. We also summarize the lessons learned during the numerous testing projects especially in the domain of business information systems.

Verteiltes Testen heterogener Systemlandschaften - von der Maßen, Thomas; Wübbeke, Andreas (Proceedings of Software Engineering 2010 (SE2010))

Cooperative feedback to improve capacity and error rate in multiuser diversity systems - an OFDM case study - Valentin, Stefan; Karl, Holger (European Transactions on Telecommunications)

Expected interference in wireless networks with geometric path loss: a closed-form approximation - S. Lichte, Hermann; Valentin, Stefan; Karl, Holger (IEEE Communications Letters)

Automated Development of Cooperative MAC Protocols - A Compiler-Assisted Approach - Simon Lichte, Hermann; Valentin, Stefan; Karl, Holger (Mobile Networks and Applications)

Concept and Prototype for a Real-Time Enabled Publish/Subscribe System - Andree, Matthias; Gebel, Alexander; Karl, Holger (10th IEEE International Conference on Computer and Information Technology, CIT 2010, Bradford, West Yorkshire, UK, June 29-July 1, 2010)

Risk Aware Overbooking for Commercial Grids - Birkenheuer, Georg; Brinkmann, Andre; Karl, Holger (Job Scheduling Strategies for Parallel Processing - 15th International Workshop, JSSPP 2010, Atlanta, GA, USA, April 23, 2010, Revised Selected Papers)

Fading-resistant low-latency broadcasts in wireless multihop networks: the probabilistic cooperation diversity approach - S. Lichte, Hermann; Frey, Hannes; Karl, Holger (Proceedings of the 11th ACM Interational Symposium on Mobile Ad Hoc Networking and Computing, MobiHoc 2010, Chicago, IL, USA, September 20-24, 2010)

FIT: Future Internet Toolbox - Biermann, Thorsten; Dannewitz, Christian; Karl, Holger (Testbeds and Research Infrastructures. Development of Networks and Communities - 6th International ICST Conference, TridentCom 2010, Berlin, Germany, May 18-20, 2010, Revised Selected Papers)

Prototyping with the Future Internet Toolbox - Dannewitz, Christian; Biermann, Thorsten; Dräxler, Martin; Beister, Frederic; Karl, Holger (Testbeds and Research Infrastructures. Development of Networks and Communities - 6th International ICST Conference, TridentCom 2010, Berlin, Germany, May 18-20, 2010, Revised Selected Papers)

Detection of Semantically Equivalent Fragments for Business Process Model Change Management - Gerth, Christian; Luckey, Markus; Küster, Jochen; Engels, Gregor
Modern business process modeling environments support distributed development by means of model version control, i.e., comparison and merging of two different model versions. This is a challenging task since most modeling languages support an almost arbitrary creation of process models. Thus, in multi-developer environments, process models or parts of them are often syntactically very different but semantically equivalent. Hence, the comparison of business process models must be performed on a semantic level rather then on a syntactic level. For the domain of business process modeling, this problem is yet unsolved. This paper describes an approach that allows the semantic comparison of different business process models using a normal form. For that purpose, the process models are fully automatically translated into process model terms and normalized using a term rewriting system. The resulting normal forms can be efficiently compared. Our approach enables the semantic comparison of business process models ignoring syntactic redundancies.

Full Semantics Preservation in Model Transformation - A Comparison of Proof Techniques - Hülsbusch, Mathias; König, Barbara; Rensink, Arend; Semenyak, Maria; Soltenborn, Christian; Wehrheim, Heike

Erfolgsfaktoren von Testprozessbewertungsmodellen - Brüseke, Frank; Sancar, Yavuz; Yigitbas, Enes (Proceedings of the Conference on Software & Systems Engineering Essentials 2010 (SEE 2010), Köln (Germany))

Towards Model-based Acceptance Testing for Scrum - Löffler, Renate; Güldali, Baris; Geisen, Silke (Softwaretechnik-Trends)

Starthilfe für modellbasiertes Testen - Güldali, Baris; Jungmayr, Stefan; Mlynarski, Michael; Neumann, Stefan; Winter, Mario (OBJEKTspektrum)

Tabellarischer Vergleich der Prozessmodelle für modellbasiertes Testen aus Managementsicht - Beulen, Dominik; Güldali, Baris; Mlynarski, Michael (Softwaretechnik-Trends)

Agiles Testen in Großprojekten mit TDD und Testaspekten: Beobachtungen und erste Erfahrungen - Späth, Melanie; Mlynarski, Michael (Softwaretechnik-Trends)

Automated acceptance testing tools for web applications using Test-Driven Development - Jureczko, Marian; Mlynarski, Michael (Electrical Review)
In the last years the software engineering community pays a strong interest in agile development methods. Those methods place software testing for example the Test-Driven Development method as an important task of the development process. Agile projects rely on good test automation tools. In this paper we evaluate five test automation tools for their usage in acceptance testing for web applications using Test-Driven Development.

Model-Based Software Product Lines Testing Survey - Oster, Sebastian; Wübbeke, Andreas; Engels, Gregor; Schürr, Andy (Model-Based Testing For Embedded Systems)

Variabilitätsmanagement in Anforderungs- und Testfallspezifikation für Software-Produktlinien - Wübbeke, Andreas
Software Product Lines (SPL) are a development paradigm allowing the reduction of the software system development time while increasing their quality. To reach these goals, the artefacts being part of many or all software systems are developed only once and reused within the different software systems. The software systems developed by a software product line approach are called products. Like a thread the reuse of artefacts is woven into the software product line development process. As some artefacts are only used for the development of some products, these artefacts constitute the variability of the SPL. First of all, the modelling of variability has to be enabled in every artefact. Beside this, dependencies can arise between variable artefacts. The modelling of variability and dependencies also demands the redevelopment or adaption of specification techniques for these artefacts. This thesis focuses on the variability management concerning requirements and test case specification for Software Product Lines. For this purpose, existing modelling languages and specification techniques are augmented with variability instead of redeveloping similar software development artefacts over and over again. In order to augment the modelling languages by variability, a language construction process based on a meta model of the variability management is defined. In order to manage the dependencies between variable artefacts, a feature based variability management is introduced. Finally, the extension of specification techniques for requirements specifications based on use case descriptions and test specifications are described. The contribution of this thesis is substantiated by a prototypical tool support and an industrial case study.

Test-driven Language Derivation with Graph Transformation-based Dynamic Meta Modeling - Engels, Gregor; Soltenborn, Christian (Proceedings of the International Colloquium on Graph and Model Transformation (GraMoT 2010), Berlin (Germany))
Deriving a new language L_B from an already existing one L_A is a typical task in domain-specific language engineering. Here, besides adjusting L_A's syntax, the language engineer has to modify the semantics of L_A to derive L_B's semantics. Particularly, in case of behavioral modeling languages, this is a difficult and error-prone task, as changing the behavior of language elements or adding behavior for new elements might have undesired side effects. Therefore, we propose a test-driven language derivation process. In a first step, the language engineer creates example models containing the changed or newly added elements in different contexts. For each of these models, the language engineer also precisely describes the expected behavior. In a second step, each example model and its description of behavior is transformed into an executable test case. Finally, these test cases are used when deriving the actual semantics of L_B - at any time, the language engineer can run the tests to verify whether the changes he performed on L_A's semantics indeed produce the desired behavior. In this paper, we illustrate the approach using our graph transformation-based semantics specification technique Dynamic Meta Modeling. This is once more an example where the graph transformation approach shows its strengths and appropriateness to support software engineering tasks as, e.g., model transformations, software specifications, or tool development.

Agility vs. Model-based Testing: A fair Play? - Güldali, Baris; Mlynarski, Michael (Proceedings of the IWK2010 Workshops: The First International Workshop on Evolution Support for Model-Based Development and Testing (EMDT2010))

Verknüpfung von kombinatorischem Plattform- und individuellem Produkt-Test für Software-Produktlinien - Wübbeke, Andreas; Oster, Sebastian (Proceedings of Produktlinien im Kontext (PIK2010))

Towards Economical Software Release Recommendations - Sancar, Yavuz; Brüseke, Frank; Voigt, Hendrik; Sauer, Stefan; Engels, Gregor (ECOOP 2010 - Workshop on Testing Object-Oriented Software Systems (ETOOS))

A Framework for Change Management of Business Process Models - Gerth, Christian (Proceedings of the Joint Workshop of the German Research Training Groups in Computer Science)

Reusing Security Requirements using an Extended Quality Model - Luckey, Markus; Baumann, Andrea; Méndez Fernández, Daniel; Wagner, Stefan (Software Engineering for Secure Systems, 2010. SESS '10. ICSE Workshop)

Teststufenspezifische Qualitätsattribute für die Qualitätsbewertung von nichtfunktionalen Anforderungen - Sancar, Yavuz; Brüseke, Frank; Engels, Gregor (Proceedings of Software-Qualitätsmodellierung und -bewertung (SQMB '10), Paderborn, Germany)

Knowledge Transfer in Global Software Development - Leveraging Ontologies, Tools and Assessments - Salger, Frank; Sauer, Stefan; Engels, Gregor; Baumann, Andrea (5th IEEE International Conference on Global Software Engineering (ICGSE 2010))
To be successful with global software development (GSD), development knowledge needs to be shared among the developers and stakeholders, and the quality of the exchanged information must be assured. Therefore, mature processes, methods and tools have to be in place. If a unified and integrated solution does not exist, this impedes the exchange of knowledge (and the migration of people between projects). In GSD, such a diversity can lead to new problems: offshore development teams have to repeatedly re-adjust to method variants used by the respective business units. This can lead to misinterpretation of information and risks for project success. We report on re-aligning the varying software engineering methods and unifying the methodology throughout Capgemini sd&m. We also standardized quality assurance procedures and tightly integrated them with the engineering methodology. By this, we arrived at a comprehensive company-wide Enterprise Software Engineering Model that effectively supports knowledge transfer from clients to the onshore and offshore team.

MDDAUI 2010 Workshop Report - Van den Bergh, Jan; Meixner, Gerrit; Sauer, Stefan (Proc. 5th Intl. Workshop on Model Driven Development of Advanced User Interfaces (MDDAUI 2010))

Pattern-based Generation of Test Plans for Open Distributed Processing Systems - Güldali, Baris; Sauer, Stefan; Winkelhane, Peter; Jahnich, Michael; Funke, Holger (Proceedings of 5th International Workshop on Automation of Software Test (AST 2010), ICSE Workshop)

Architecture-Driven Derivation of Performance Metrics - Brüseke, Frank; Sancar, Yavuz; Engels, Gregor (Proceedings of Software-Qualitätsmodellierung und -bewertung (SQMB '10), Paderborn, Germany)

Effort Comparison of Model-based Testing Scenarios - Güldali, Baris; Mlynarski, Michael; Sancar, Yavuz (Proceedings of 3th International Conference on Software Testing, Verification, and Validation Workshops)

Test Case Generation for Visual Contracts Using AI Planning - Schnelte, Matthias; Güldali, Baris (INFORMATIK 2010, Beiträge der 40. Jahrestagung der Gesellschaft für Informatik e.V. (GI))

Proceedings of the 22nd ACM symposium on Parallelism in algorithms and architectures - SPAA '10 - Meyer auf der Heide, Friedhelm; Phillips, Cynthia A.

Preprocessed Global Visibility for Real-Time Rendering on Low-End Hardware - Eikel, Benjamin; Jähn, Claudius; Fischer, Matthias (Advances in Visual Computing)
We present an approach for real-time rendering of complex 3D scenes consisting of millions of polygons on limited graphics hardware. In a preprocessing step, powerful hardware is used to gain fine granular global visibility information of a scene using an adaptive sampling algorithm. Additively the visual influence of each object on the eventual rendered image is estimated. This influence is used to select the most important objects to display in our approximative culling algorithm. After the visibility data is compressed to meet the storage capabilities of small devices, we achieve an interactive walkthrough of the Power Plant scene on a standard netbook with an integrated graphics chipset.

Computergestützte traumatherapeutische Behandlungsmöglichkeiten bei Verkehrsunfallopfern von Kindern und Jugendlichen - Huck, Wilfried; Alakbarov, Alexej; Domik, Gitta; Radkowski, Rafael; Tölke, Roswitha; Mikus, Ann-Cathrin; Geisen, Silke (12. Jahrestagung der Deutschsprachigen Gesellschaft für Psychotraumatologie (DeGPT))

Proof-Carrying Hardware: Concept and Prototype Tool Flow for Online Verification - Drzevitzky, Stephanie; Kastens, Uwe; Platzner, Marco (International Journal of Reconfigurable Computing)

Virtuelle Speicherverwaltung für Hardware Threads in Rekonfigurierbaren Systemen - Agne, Andreas

EMG-basierte Ganganalyse - Boschmann, Alexander

Evolvable Cache Controller - Breitlauch, Daniel

Soft Microprocessors with tightly coupled Application-Specific Coprocessors - Dridger, Denis

Parallelization of the UCT Algorithm on HPC-Clusters - Graf, Tobias

Fluctuating EMG Signals: Investigating Long-term Effects of Pattern Matching Algorithms - Kaufmann, Paul; Englehart, Kevin; Platzner, Marco (International Conference of the IEEE Engineering in Medicine and Biology Society (EMBC))

A Novel Hybrid Evolutionary Strategy and its Periodization with Multi-objective Genetic Optimizers - Kaufmann, Paul; Knieper, Tobias; Platzner, Marco (IEEE World Congress on Computational Intelligence (WCCI), Congress on Evolutionary Computation (CEC))

Selected papers from the 18th International Conference on Field Programmable Logic and Applications, FPL 2008 (editorial) - Kebschull, Udo; Platzner, Marco; Teich, Jürgen (IET Computers Digital Techniques)

Hybridization of Global Multi-Objective and Local Search Techniques - Knieper, Tobias

Coping with Resource Fluctuations: The Run-time Reconfigurable Functional Unit Row Classifier Architecture - Knieper, Tobias; Kaufmann, Paul; Glette, Kyrre; Platzner, Marco; Torresen, Jim (IEEE Intl. Conf. on Evolvable Systems (ICES))

ReconOS: An Operating System for Dynamically Reconfigurable Hardware - Lübbers, Enno; Platzner, Marco (Dynamically Reconfigurable Systems: Architectures, Design Methods and Applications)

FPGA/CPU Multicore-Plattform für ReconOS/eCos - Meiche, Robert

Transparente Hardwarebeschleunigung durch Shared Library Interposing - Niekamp, Manuel

A Token-Ring Network-On-Chip for Message Passing in ReconOS - Runde, Bodo

Scheduling Support for Heterogeneous Hardware Accelerators under Linux - Wiersema, Tobias

Dynamically Reconfigurable Systems: Architectures, Design Methods and Applications

Sub-threshold charge recovery circuits - Khatir, Mehrdad; Ghasemzadeh Mohammadi, Hassan; Ejlali, Alireza (Computer Design (ICCD), 2010 IEEE International Conference on)

On the Impact of Human Driver Behavior on Intelligent Transportation Systems - Dressler, Falko; Sommer, Christoph (2010 IEEE 71st Vehicular Technology Conference)

Emissions vs. Travel Time: Simulative Evaluation of the Environmental Impact of ITS - Sommer, Christoph; Krul, Robert; German, Reinhard; Dressler, Falko (2010 IEEE 71st Vehicular Technology Conference)

On the feasibility of UMTS-based Traffic Information Systems - Sommer, Christoph; Schmidt, Armin; Chen, Yi; German, Reinhard; Koch, Wolfgang; Dressler, Falko (Ad Hoc Networks)

Improving the Accuracy of IVC Simulation Using Crowd-sourced Geodata - Sommer, Christoph; Eckhoff, David; Dressler, Falko (PIK - Praxis der Informationsverarbeitung und Kommunikation)

An Analysis of the FURIA algorithm for fuzzy rule induction - Hüllermeier, Eyke; Hühn, J. (Advances in Machine Learning I: Dedicated to the Memory of Professor Ryszard S.Michalski)